A tribute to Ralph Vaughan Williams (1872-1958), Gustav Holst (1874-1934) and Percy Scholes (1877-1958) - Tracey, Hugh (International Library of African Music, 1958)
The lives of all three as composers and writers may seem to have their settings far removed from Africa and its distinctive folk music styles. Yet a common element which made them great, and is equally important for Africa, was a clear and practical understanding of the true position of folk musics in the whole gamut of musical practice.
Keywords: Ethnomusicology; African Music